1997
DOI: 10.1104/pp.114.3.937
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Declines in Soybean N2 Fixation Are Related to Nodule Sucrose Synthase Activity

Abstract: Fixation of N, by legume root nodules can be rapidly and severely inhibited by a range of environmental perturbations, including defoliation, drought, salinity, and application of nitrate. Stress can also be induced by experimental approaches such as placing plants in prolonged darkness (Gordon et al., 1993;Gogorcena et al., 1997). One explanation for this decline in N, fixation in response to stress is that the ODB operates to reduce O, flux into the nodule and thus prevent damage to nitrogenase activity Hunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
94
2
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 47 publications
10
94
2
2
Order By: Relevance
“…In addition, L. japonicus presented higher SS and AI activities than M. truncatula, in accordance with its higher nitrogenase activity. It has been previously hypothesized that there is a close link between ANA and the capacity of the nodule to metabolize sucrose (Gordon et al 1997. In particular, SS activity was more sensitive to salt stress as compared with AI, in agreement with previous works that have established that nodule sucrose synthase are particularly sensitive to stress (Gonza´lez et al 1995;Gordon et al 1997).…”
Section: Lo´pez and C Lluchsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, L. japonicus presented higher SS and AI activities than M. truncatula, in accordance with its higher nitrogenase activity. It has been previously hypothesized that there is a close link between ANA and the capacity of the nodule to metabolize sucrose (Gordon et al 1997. In particular, SS activity was more sensitive to salt stress as compared with AI, in agreement with previous works that have established that nodule sucrose synthase are particularly sensitive to stress (Gonza´lez et al 1995;Gordon et al 1997).…”
Section: Lo´pez and C Lluchsupporting
confidence: 81%
“…A strong correlation between sugar accumulation and osmotic stress tolerance has been widely reported (Gilmour et al 2000;Streeter et al 2001;Taji et al 2002), which support a higher tolerance of L. japonicus nodules to salt stress. M. truncatula nodules did not show nodule carbohydrate accumulation; however, amino acids accumulated in these nodules by NaCl, which could be explained as a consequence of damage produced by saline stress, in accordance with results of Gordon et al (1997), Soussi et al (1998) and Khadri et al (2007) in nodules of soybean, chickpea and common bean, respectively.…”
Section: Lo´pez and C Lluchsupporting
confidence: 69%
See 1 more Smart Citation
“…Studies on soybean (Glycine max), common bean (Phaseolus vulgaris), and pea (Pisum sativum) have shown that the inhibitory effects may be mediated by a decrease in nodule O 2 permeability (Durand et al, 1987;Serraj and Sinclair, 1996;Ramos et al, 1999) and metabolic activity (Díaz del Castillo and Layzell, 1995). The finding that the activity of Suc synthase (SS), but not other carbon and nitrogen metabolism enzymes, rapidly declined in nodules upon imposition of stress provided strong evidence for a major role of SS in the inhibition of N 2 fixation (González et al, 1995;Gordon et al, 1997;Ramos et al, 1999). A detailed biochemical analysis of the rug4 mutant of pea, which displays severely reduced SS activity, further demonstrated an essential role of SS in symbiosis .…”
mentioning
confidence: 96%
“…Many other important alterations related to oxygen, carbon, and nitrogen metabolism occur in nodules during senescence, but the precise sequence of these biochemical changes is far from clear (Carroll et al, 1987;Layzell et al, 1990;Gordon et al, 1997). There is also a paucity of information regarding the structural changes involved in stressinduced nodule senescence.…”
mentioning
confidence: 99%